Neural circuit rewiring: insights from DD synapse remodeling. Issue 1 (2nd January 2016) - Kurup, Naina; Jin, Yishi
ABSTRACT: Nervous systems exhibit many forms of neuronal plasticity during growth, learning and memory consolidation, as well as in response to injury. Such plasticity can occur across entire nervous systems as with the case of insect metamorphosis, in individual classes of neurons, or even at the level of a single neuron. A striking example of neuronal plasticity in C. elegans is the synaptic rewiring of the GABAergic Dorsal D-type motor neurons during larval development, termed DD remodeling. DD remodeling entails multi-step coordination to concurrently eliminate pre-existing synapses and form new synapses on different neurites, without changing the overall morphology of the neuron. This mini-review focuses on recent advances in understanding the cellular and molecular mechanisms driving DD remodeling.